Development of innovative learning media based on video applications in the introduction to the usage of sewing tools course for fashion students in the state university of malang - Hadijah, Idah; Supadmi Irianti, Agus Hery; Aini, Nurul; Yulianingrum Pradani, Rizky; Sapitra Wahyu Ilyasari, Nurlaila Indra; Septiana Dwi Anggraini, Wimma (International Journal of Scientific Research and Management (IJSRM), 2022)
The media make it easier for students and lecturers in the student-centered online teaching and learning process, in sewing equipment courses. it is necessary to develop learning media based on video tutorials for operating high speed sewing machines to facilitate online learning. The purpose of this research is to develop three applicable video tutorial products (VTA) namely (overlock sewing machine operation, overdeck sewing machine operation, and buttonhole machine operation). The method used is the ADDIE learning media development model. The results from expert's validation related to media  73.8%, related to material  category  96. 8%, and  feasible category 89.01%.. The discussion of applicative video tutorials for the operation of overlock sewing machines, overdeck sewing machines, and buttonhole machines begins with the initial display/opening, presentation of sewing machine operation material, ends with assignments/practice. Video displays are made to facilitate and improve students' understanding and motivation in learning. This is because video is one of the efforts to increase understanding and interest in learning for students, which is a technology for capturing, recording, processing, transmitting and rearranging moving images, which are related to vision. and hearing, so that the video is suitable to be used for learning the introduction/use of sewing machines in sewing equipment courses.